Gel-based microarrays in clinical diagnostics in Russia. (November 2011) - Gryadunov, Dmitry; Dementieva, Ekaterina; Mikhailovich, Vladimir; Nasedkina, Tatiana; Rubina, Alla; Savvateeva, Elena; Fesenko, Eugeny; Chudinov, Alexander; Zimenkov, Danila; Kolchinsky, Alexander; Zasedatelev, Alexander
Immobilization of molecular probes in 3D hydrogel elements provides some essential advantages compared with conventional flat surfaces. In this article, an integrated technology based on the use of low-density microarrays comprised of hemispherical gel elements, developed at the Engelhardt Institute of Molecular Biology (Moscow, Russia) for various applications will be reviewed. The structure of the gel can be adapted for immobilization of virtually any biological molecules in a natural hydrophilic environment. The discrimination between matching and mismatching duplexes of nucleic acids in these conditions is more reliable than on conventional flat surfaces, minimizing the number of elements needed to detect specific sequences. Protein molecules immobilized in hydrogel-based biochips better preserve their biological properties. As described in this article, such biochips were successfully applied for laboratory diagnostics in a wide variety of clinical conditions involving the identification of bacterial and viral pathogens, cancer-related mutations and protein tumor markers.